دراسة تحليلية للموازنة العامة في ظل جائحة كوفيد - 19 -دراسة حالة الجزائر- - أحلام عنتري; لبنى حميداني (My University, 2021)
The crisis that has been going on since the summer of 2014, this crisis has severely affected the Algerian economy, more precisely, in tax revenues from the export of hydrocarbons, in this context, the Algerian government has adopted a number of measures and mechanisms in this regard to remedy this deficit and relieve pressure on the public budget for the state, this study found that these rationalization measures taken by the Algerian authorities in the face of the setback what oil prices have known from 2014 to 2020, they are only successful in the short term, these are measures that do not enjoy popular support and may be the cause of cases of global health crisis coincided with the COVID 19 pandemic, with the severe oil price collapse political and social instability. ............................................................... تزامن تفشي الأزمة الصحية العالمية جائحة كوفيد - 19 - مع أزمة انهيار أسعار النفط الحادة التي لا تزال مستمرة منذ صيف 2014 ، وقد أث رت هذه الأزمة على نحو حاد في الاقتصاد الجزائري، وبوجه أدق في عائدات الضرائب من تصدير المحروقات، وفي هذا الإطار انتهجت الحكومة الجزائ رية حيال ذلك جملة من الإجراءات والآليات لعلاج هذا العجز وتخفيف الضغط على الموازنة العامة للدولة، وقد توصلت هذه الدراسة إلى أن هذه الإجراءات الترشيدية التي اتخذتها السلطات الجزائرية في مواجهة الانتكاسة التي عرفتها أسعار النفط منذ 4102 إلى ااية 4141 هي إجراءات ناجحة فقط في المدى القصير، وهي إجراءات لا تحظى بالدعم الشعبي وقد تكون سببا في حدوث حالات من عدم الاستقرار السياسي والاجتماعي